2022
DOI: 10.1017/ash.2022.26
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of active versus passive methods of responding to rapid diagnostic blood culture results

Abstract: Objective: To compare 2 methods of communicating polymerase chain reaction (PCR) blood-culture results: active approach utilizing on-call personnel versus passive approach utilizing notifications in the electronic health record (EHR). Design: Retrospective observational study. Setting: A tertiary-care academic medical center. Patients: Adult patients hospitalized with ≥1 positive blood culture containing a gram-positive organism identified by PCR betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Multiple recent studies have shown the positive effects of real-time, active methods to assist with optimizing antibiotic stewardship practices using rapid diagnostic tests. [15][16][17] These efforts by antibiotic stewardship clinicians can help decrease the initial hesitancy of some providers to embrace these new technologies and assist with their appropriate application to antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have shown the positive effects of real-time, active methods to assist with optimizing antibiotic stewardship practices using rapid diagnostic tests. [15][16][17] These efforts by antibiotic stewardship clinicians can help decrease the initial hesitancy of some providers to embrace these new technologies and assist with their appropriate application to antibiotic use.…”
Section: Discussionmentioning
confidence: 99%